2015
DOI: 10.1186/s12888-015-0447-4
|View full text |Cite
|
Sign up to set email alerts
|

Predicting general criminal recidivism in mentally disordered offenders using a random forest approach

Abstract: BackgroundPsychiatric expert opinions are supposed to assess the accused individual’s risk of reoffending based on a valid scientific foundation. In contrast to specific recidivism, general recidivism has only been poorly considered in Continental Europe; we therefore aimed to develop a valid instrument for assessing the risk of general criminal recidivism of mentally ill offenders.MethodData of 259 mentally ill offenders with a median time at risk of 107 months were analyzed and combined with the individuals’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 22 publications
1
36
0
1
Order By: Relevance
“…Machine-learning studies in the domain of substance use are based on the use of regularized regression models (i.e. For instance, random forests (RF), support vector machines (SVMs) and artificial neural networks (ANN) are being used for prediction in other areas of health sciences [31][32][33]. These algorithms provide explicit control over the complexity of the fitted model and deliberately promote simpler and more interpretable solutions compared to non-regularized models.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Machine-learning studies in the domain of substance use are based on the use of regularized regression models (i.e. For instance, random forests (RF), support vector machines (SVMs) and artificial neural networks (ANN) are being used for prediction in other areas of health sciences [31][32][33]. These algorithms provide explicit control over the complexity of the fitted model and deliberately promote simpler and more interpretable solutions compared to non-regularized models.…”
Section: Introductionmentioning
confidence: 99%
“…However, previous substance use machine-learning studies fail to consider algorithms other than regularized regression models. For instance, random forests (RF), support vector machines (SVMs) and artificial neural networks (ANN) are being used for prediction in other areas of health sciences [31][32][33]. Considering the complexity of pathological mechanisms and non-linearity of the predictive effects, these techniques might improve the chances of prediction of pathological trajectories, treatment response and matching patients to the most effective treatments [34].…”
Section: Introductionmentioning
confidence: 99%
“…Desde el mismo se promulga la existencia de ocho variables que explicarían de manera significativa el riesgo de reincidir, entre estas aparecen: a) historia individual de conducta antisocial, b) patrón de personalidad antisocial, c) cognición antisocial, d) redes o vínculos antisociales, e) ámbito familiar relacionado con bajo nivel de satisfacción, f) dificultades en el ámbito escolar y laboral, g) manejo del tiempo de ocio, h) abuso de sustancias psicoactivas En esta línea, los resultados de estudios, como el realizado por Mastrorilli, et al 46 , encontraron que la carrera pro-criminal emerge como un fuerte predictor. Ratificado por Pflueger, et al 47 , cuando en los resultados de su estudio de corte longitudinal "Predicting general criminal recidivism in mentally disordered offenders using a random forest approach" concluyeron que las variables con mayor nivel de predicción de la reincidencia corresponden a historial pro-criminal, edad y versatilidad delictiva. Esta última variable, retomada de forma general en el estudio de Olson, et al 48 , cuya investigación "Comparing male and female prison releasees across risk factors and postprison recidivism" concluye, a partir de una muestra de 26.534 infractores entre los 35 y 50 años, que el historial criminal extenso aumenta la probabilidad de reincidir.…”
Section: Aspectos Criminogénicos De La Reincidenciaunclassified
“…Establishing a negative relationship between psychiatric diagnosis and recidivism would help mitigate the stigma surrounding persons with a mental health disorder and the supposed dangers inherent in their condition (Fazel & Yu, 2011). However, it is important to note that other studies on the relationship between the presence of mental health problems and recidivism have found that inmates with a psychiatric disorder are more prone to reoffending and repeat incarceration compared with individuals with a psychiatric disorder but no previous incarceration (Baillargeon, Binswanger, Penn, Williams, & Murray, 2009;Pflueger, Franke, Graf, & Hachtel, 2015;Segeren, de Wit, Fassaert, & Popma, 2017).…”
Section: Introductionmentioning
confidence: 99%